Reinventing Ethical Substance of Pancasila in Article 33 of the 1945 Constitution: a Study of Indonesia’s Actual Economic System Based on Honneth’s Young Hegelian Concept of Social Recognition - Alexander Seran (Syntax Idea)
We observe social conflicts arise for a myriad of reasons such as politics, economics, and differing cultural and religious identities. This essay is elaborated through a critical interpretation of Indonesian political economy as it is written in Article 33 of the 1945 Constitution of Indonesia. It reflects Indonesia’s commitment to ensuring that economic benefits are distributed equitably among citizens. Using Axel Honneth’s young Hegelian concept of recognition by love, respect, and solidarity, Pancasila as a system of ethics can be used to meet Honneth’s theory of moral grammar for social and economic conflicts resolution